2010
DOI: 10.1021/ie1016865
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogenation of p-Chloronitrobenzene on Mo-Doped NiB Cluster Catalysts

Abstract: The objective of this study was to investigate the effect of Mo content on the catalytic properties of Mo-NiB nanoclusters in the hydrogenation of p-chloronitrobenzene. A series of Mo-doped NiB nanoalloy catalysts with various Mo contents were prepared by chemical reduction method. An excess amount of NaBH 4 was used (B/Ni atomic ratio ) 3) to fully reduce Ni. Even adding a small amount of Mo on NiB had a significant effect on the activity and selectivity to p-chloroaniline. The catalyst with the atomic ratio … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 20 publications
1
9
0
Order By: Relevance
“…The same group also studied tungsten-modified Ni-Co-B-catalysts for the reduction of 4-chloronitrobenzene (vide infra) . In 2011, they investigated molybdenum-doped Ni-B cluster catalysts with different Mo/Ni ratios . The synthetic methodology was again comparable to the other systems, starting from a methanolic solution of nickel acetate and ammonium heptamolybdate.…”
Section: Heterogeneous Nickel-based Catalystssupporting
confidence: 68%
“…The same group also studied tungsten-modified Ni-Co-B-catalysts for the reduction of 4-chloronitrobenzene (vide infra) . In 2011, they investigated molybdenum-doped Ni-B cluster catalysts with different Mo/Ni ratios . The synthetic methodology was again comparable to the other systems, starting from a methanolic solution of nickel acetate and ammonium heptamolybdate.…”
Section: Heterogeneous Nickel-based Catalystssupporting
confidence: 68%
“…Chemoselectivity in amine production is particularly relevant in the hydrogenation of p-chloronitrobenzene 70 where a range of intermediates and by-products, notably nitrobenzene and aniline, have been reported for reaction over Pd and Ni catalysts in both liquid and gas phases. 28,53,71,72 A simplified reaction pathway is presented in Fig. 7(A), where the target p-chloroaniline formed via -NO 2 reduction (step I) can undergo hydrodechlorination to aniline (step II) or alternatively nitrobenzene is first generated by hydrodechlorination (step III) with subsequent hydrogenation to aniline (step IV).…”
Section: Catalytic Responsementioning
confidence: 99%
“…Particularly, the fabrication of highly active and stable catalysts plays a key role for their industrial applications. For example, Chen et al [8] investigated the effect of Mo content on the catalytic performance of NiB nanoclusters in the hydrogenation of p-chloronitrobenzene and found that the addition of Mo can markedly improve the activity and selectivity of NiB catalyst. [1][2][3][4][5] Although some of them have been applied, the high prices of noble metals have limited their further applications, making it desirable to search for more economical alternatives.…”
Section: Introductionmentioning
confidence: 99%